Processo Civil e Constituição Federal de 1988 : diálogo necessário na pós-modernidade - Macedo, Fernanda dos Santos (2013)
The scientific research on the dialogue between the Brazilian Civil Procedure and the Constitution of the Federative Republic of Brazil of the 1988 in the context of Postmodernity shown of unique importance because, actuality, there is talk about a paradigm of the Brazilian Civil Procedure which has aimed at solving conflicts effectively, timely and appropriate. Thus, the cut research out of aims at identifying the Brazilian Civil Procedure and the Constitution of the Federative Republic of Brazil of the 1988 should establish a dialogue necessary not only in the theoretical field, but also in practice, because the search for a pattern of Civil Procedure has meet the demands of current social. In this sense, shows the characteristics of Postmodernity, which are responsible for defining the panorama that establishes the main analysis of dialogue between the Brazilian Civil Procedure and the Constitution of the Federative Republic of Brazil of the 1988. Moreover, analyzes the primary features of the Constitution of the Federative Republic of Brazil of the 1988 to the Brazilian legal system, as well as its relationship with the national Civil Procedure, considering as a link between the two institutes of the Constitutional Guarantees of the Jurisdiction and of the Process. Also, discusses the trend of the Brazilian Civil Procedure in the Postmodernity, explaining not only the behavior of the Jurisdiction Postmodern, but the species of conflicts of interests are available in the post-modern. Moreover, it is clear that the necessary dialogue between the Brazilian Civil Procedure and the Constitution of the Federative Republic of Brazil of the 1988 now requires an analysis of the legislative civil procedural content in order to determine whether the legislative contemporary production respects the constitutional procedural commandments. Thus, there is, in the end, that the paradigm of the Brazilian Civil Procedure Postmodernity is that it promotes the realization of Constitutional Guarantees of the Jurisdiction and the Procedure, particularly in the practical performance of procedural agents and their assistants, with the objective to resolve conflicts of interest effectively, timely and appropriate.